Hakikat Pendidik Dalam Pendidikan Islam - Muhammad Ali (Tarbawiyah Jurnal Ilmiah Pendidikan, 2014)
A teacher is not only transfering knowledge to students but also how to educate her students to be good people. So that, the students will be a good people who have knowledge and religi. In islamic education, the students not only gived intelegensi capability but also emosional intelegensi, social and spiritual.